1989
DOI: 10.1111/j.1365-2672.1989.tb02491.x
|View full text |Cite
|
Sign up to set email alerts
|

The mycoflora of gari

Abstract: Mycological studies have been carried out on market samples of gari, a ready‐to‐use staple fermentation product of cassava (Manihot esculenta cranz). Commercial and industrial samples were analysed. The moisture contents of samples varied from 7% to 17% while the water activity (aw) varied from 0·52 to 0·85 and the pH of samples ranged from 3·9 to 7·26. Several fungi were isolated from the commercial samples while the industrial packaged samples were relatively mould‐free. Moulds isolated were mainly Aspergill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These phenomena are no doubt associated with the greater percentage of gelatinization which occurs at longer cooking times. The acceptable range of colour values quoted by Codex Alimentarius (1986), Chuzel et al (1988) and Sanni (1989), are: L* 80-85, b* 17-21. Cooking times greater than 15 minutes gave colour properties which fell beyond the accepted range.…”
Section: Colourmentioning
confidence: 93%
See 1 more Smart Citation
“…These phenomena are no doubt associated with the greater percentage of gelatinization which occurs at longer cooking times. The acceptable range of colour values quoted by Codex Alimentarius (1986), Chuzel et al (1988) and Sanni (1989), are: L* 80-85, b* 17-21. Cooking times greater than 15 minutes gave colour properties which fell beyond the accepted range.…”
Section: Colourmentioning
confidence: 93%
“…This, and earlier studies, found that pH and total titratable acidity could however vary quite widely because they depend on the duration of the fermentation stage, which also varies widely to suit different tastes, and also depends on the nature of mycofloras which occur. A previous study by Sanni (1989) showed that the pH of market sam-ples varied from 3.9 to 7.3, with the peak between 3.5 and 4.5.…”
Section: Ph and Total Titratable Aciditymentioning
confidence: 98%
“…The preparation of garri includes the detaching of the root, washing, crushing, fermentation, removal of water and, roasting (Oyewole and Sanni 1995). Fufu is another major staple fermented food from cassava that is consumed by most people in Africa (Lancaster et al 1982, Okafor et al 1984, Sanni 1989, Longe 1990, Oyewole 1995, and the processing includes peeling, breaking into small sizes, soaking, pulping, screening, sedimentation, removal of water and production of cassava paste (Oyewole et al 2001). The processing of lafun is almost similar to the preparation of fufu but the fermented cassava needs to be sun-dried and milled before consumption (Oyewole and Sanni 1995) Therefore, the present study intends to establish the micro flora of these popular cassava products in Nigeria, and to determine their proximate content and microbiological safety to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Several books (HESSELTINE and WANG, 1986;REDDY et al, 1986;STEINKRAUS, 1983;WOOD, 1985) and reviews (BEUCHAT, 1987; V A N and KADAM, 1989;NOUT andROM-BOUTS, 1990: SANNI, 1993) have been published on the subject of indigenous fermented foods. A book describing applications of biotechnology to traditional fermented foods was published by the U S .…”
mentioning
confidence: 99%